2019
DOI: 10.22161/ijeab.4443
|View full text |Cite
|
Sign up to set email alerts
|

Modelling of Orthometric heights from Multi-Networks of GNSS/Precise Levelling in FCT, Abuja

Abstract: The geoid is used as a transformation linkage between ellipsoidal heights (h) determined from DGPS observations and orthometric heights (H). Widespread acceptability and adoption of GPS in local geospatial data acquisitions require the development of a local geoid model (N) for use to obtain orthometric heights in the absence of a national geoid model. Geoid model can be developed by gravimetric approach; global geopotential model (GGM); geometric technique among others. The conventional approach to GPS measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 2 publications
0
12
0
Order By: Relevance
“…A study has stated that a small area is the one that is less than 200km 2 in size (Schofield, 2007). In surface fitting methods, models adopted depend on the size and nature of the variation of the heights of the points used as opined Oluyori (2019). As such, Romans (2007) suggested that for small areas, models with four parameters or lower, be adopted for better accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…A study has stated that a small area is the one that is less than 200km 2 in size (Schofield, 2007). In surface fitting methods, models adopted depend on the size and nature of the variation of the heights of the points used as opined Oluyori (2019). As such, Romans (2007) suggested that for small areas, models with four parameters or lower, be adopted for better accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…The geographic location and size of a project area may point to the need for adoption of different polynomial interpolation surfaces used for different regions instead of single surface model to cover all. The ideal scenario is however, for a single geoid model to cover a study area which was achieved by Oluyori (2019).…”
Section: Methodsmentioning
confidence: 99%
“…However, circumstances in practical reality may make homogeneity impossible/infeasible (location of various classes of controls) and therefore the need to investigate the implication of such occurrences is desirable by computing accuracy/standard deviations (σ). Geoid modelling by Nwilo (2013), Eteje et al (2018), Oluyori (2019), and others may be applied to modernization of heights to produce orthometric heights by reference to vertical datum when adopting Global Positioning System (GPS) technology. GPS technology produces three dimensional coordinates (N, E, h) relative to earth ellipsoid.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations